Attending veterinarians improve the research capability and psychological well-being of researchers in animal research institutes - Lee, Ji Min; Lee, Gwang-Hoon; Kim, KilSoo (Frontiers in Veterinary Science, 2024)
The use of laboratory animals in biomedical research has significantly advanced scientific understanding, yet it raises ethical concerns about animal welfare and the mental health of researchers Recent research has highlighted the potential for stress and compassion fatigue among researchers working with distressed animals. Attending veterinarians (AVs) are crucial in mitigating the pain and stress experienced by animals and, by extension, researchers. However, the impact of AVs on researchers' psychological well-being remains understudied. This study explores how AVs contribute to researchers' research capability and psychological well-being in animal research institutions. AVs oversee animal housing, health, and welfare; their involvement is mandated or strongly recommended in developed countries. AVs enhance animal welfare by ensuring proper housing, nutrition, and social interaction. They monitor animal health, educate researchers on pain assessment, and promote compliance with post-surgical care. AVs also contribute to researchers' well-being by addressing euthanasia procedures, which can be emotionally challenging. Programs for rehoming animals after experiments offer an alternative to euthanasia and positively impact researchers' psychological wellbeing. Moreover, AVs promote workplace well-being by fostering positive workplace cultures, offering peer counseling, and providing social support. Programs considering animal welfare and researchers' emotions are crucial for a healthy research environment. In conclusion, AVs are essential in balancing scientific progress with animal welfare and researchers' psychological well-being. Therefore, their role should be recognized as vital in achieving social equity that considers the welfare of humans and laboratory animals.